Can the Meat from Angus Crossbreds with Bos indicus Dams Compete with that from Bos taurus Dams in Organoleptic Properties and Fatty Acid Profile? - CHAIWANG, Niraporn; BUNMEE, Thanaporn; SAMOOTKWAM, Kittipong; TIPNATE, Bulgul; WARITTHITHAM, Amphon; KREUZER, Michael; JATURASITHA, Sanchai (Walailak Journal of Science and Technology (WJST), 2018)
It was experimentally determined whether crossbreeding with Bos indicus dams compared to Bos taurus dams may provide meat which is competitive in organoleptic properties and fatty acid (FA) profile and if tenderness, assumed to be lower, is really adversely affected. Eight Black Angus × White Lamphun (A×W) bulls were compared with 8 Black Angus × Holstein Friesian (A×H). M. longissimus thoracis, M. semimembranosus and M. infraspinatus were analyzed for organoleptic properties and objective explanatory properties related to tenderness, as well as FA profile. Tenderness was judged lower in the M. infraspinatus of A×W than A×H, but not in the other muscles. Shear force and collagen solubility tended (P < 0.10) to be lower in all 3 muscles of A×W compared to those of A×H. The fat content of the M. longissimus thoracis from A×W was lower than that from A×H. The lipids in the M. longissimus thoracis from A×W were richer in polyunsaturated FA and total n-3 FA, and poorer in C18:0 and saturated FA than those of A×H. Furthermore, the lipids of the M. semimembranosus from A×W had higher proportions of C14:1 and C16:1 than that of A×H. The FA in the M. infraspinatus from A×W had higher proportions of C18:3 n-3, mono-unsaturated FA and total n-3 FA and the proportion of saturated FA was lower than in A×H. The M. infraspinatus from A×W was lower in cholesterol content than that from A×H. There were some differences in tenderness (inferior in White Lamphun crossbreds) and FA profile (superior in White Lamphun crossbreds), but differences were numerically small and, thus, may be of low practical relevance. Therefore, crossbreeding with indigenous Bos indicus cattle does not seem to be restricted by low meat quality.